EXTREME MATERIAL POVERTY AS A NEGATIVE PREREQUISITE FOR THE TRANSFER OF AN APPLICANT FOR INTERNATIONAL PROTECTION TO THE COMPETENT MEMBER STATE AND FOR THE REJECTION OF AN APPLICATION FOR THE GRANT OF REFUGEE STATUS AS BEING INADMISSIBLE - Wróbel, Izabela Małgorzata (Review of European and Comparative Law, 2019)
The essential measures for a common European asylum system adopted by the EU institutions include the Regulation (EU) No 604/2013 and the Directive 2013/32/EU. These acts relate to the various stages of the functioning of the common European asylum system, however, there may be a risk of a violation of the fundamental rights of applicants as set out in the Charter of Fundamental Rights of the EU, including the prohibition of inhuman or degrading treatment (Article 4 of the Charter), at both stages. Such a risk may arise as a result of deficiencies in asylum systems of the Member States. If these deficiencies are to fall within the scope of Article 4 of the Charter, they must attain a particularly high level of severity, which depends on all the circumstances of the case. An example of attaining this particularly high level of severity is the situation of extreme material poverty. As acts of the EU asylum law do not contain the terms “particularly high level of severity” and “extreme material poverty” and all the more they do not define them, guidelines on how to interpret and apply Article 4 of the Charter in the context of the common European asylum system should be sought in the case law of the Court of Justice of the EU. Therefore, the aim of the article is to explore and attempt to generalise and develop the basis and the criteria indicated by the CJEU for assessing the actual nature of deficiencies in the asylum system of the Member State in question from the point of view of the prohibition laid down in Article 4 of the Charter, with particular emphasis on the criterion of a particularly high level of severity and the situation of extreme material poverty which meets this criterion.